Market Imperfections and Employment - Geroski, Paul (OECD Jobs Study Working Papers, 1995)
This working paper addresses the question whether imperfect competition in product markets contributes substantially to the level and persistence of unemployment in modern industrial economies. In section I, the paper documents the available empirical research of the origin and extent of product market power held by firms due to market imperfections. The implications for employment are then explored through transmission of such power into the labour market through wages (section 2) and output reduction from pricing above marginal cost or wage levels below marginal revenue product (section 3). The role for such product market power in the macroeconomic analysis of unemployment is also explored in section 3, but little evidence of the importance on the macro level is available. The paper thus assesses the extent of product market imperfections and their importance in wage setting. It concludes that product market imperfections are widespread and although large deviations of price ...